Impact of Firm Characteristics on IPO’s Short Run Performance: Evidence from Pakistan - KAMRAN FAROOQ; SAEED AKBAR; KIRAN ALIM; SOURATH (Journal of Business & Tourism, 2021)
In present day world, the concept of initial public offering (IPO's) has got much significance since its execution altogether influence the success of the companies. The current study aims at conducting a nonsystematic review of literatures on the concept of short runs performance of initial public offering in Pakistan. In this regard, we studied the IPO’s of 77 companies listed at Pakistan Stock Exchange (PSX) from the period of 2000-2015. The finding shows a positive and significance relationship between size of the firm and underwriter reputation while the age of the firm and risk shows negative relationship with the dependent variable MAAR. The performance of initial public offerings has significant effect on success or failure of a company. In this way, the companies in modern corporate world can ensure their success through effective utilization of initial public offerings.